Advancing "Intersectional Servingness" in Research, Practice, and Policy With Hispanic-Serving Institutions - Gina A. Garcia; Marcela G. Cuellar (SAGE Publishing, 2023)
There has been a surge in the number of Hispanic-serving institutions (HSIs), which are degree-granting, nonprofit, postsecondary institutions that enroll at least 25% Hispanic/Latinx/e undergraduate students. Although HSI scholarship has increased dramatically since around 2010, there is still a gap in knowledge about individuals who fall within the "H" and the diversity among HSIs themselves. Using critical theory and critical methods, the articles in this special topic collection explore the complexities of the Hispanic/Latinx/e identity and the various ways that HSIs fall short of and meet the challenges of serving students at the intersections of identity. This introduction provides a brief overview of the eight articles in this collection and explains the need for this critical approach to HSI scholarship, which we call "intersectional servingness." We outline the contributions of these eight articles and call on practitioners, scholars, policy intermediaries, funders, and federal agencies to consider the complexities of the "H" while making decisions, advancing research, implementing policies, and creating funding streams that will enhance intersectional servingness.